Answer:
X= 15
K=45
Step-by-step explanation:
The Triangle Sum Theory means that every interior angle of a triangle sums up to 180. My first approach was to put 169 as x but that isn’t correct. That is because a triangle’s smallest angles have to add up to be more than the biggest angle. Ex (10, 5, 7 that is a triangle because the sum of 5+7 is more than 10) So as you can see there are x’s next to the other numbers. That is because x needs to be able to multiply with the other numbers and stand on it’s own and add up to 180. So this would be the equation: X+8•X+3•X=180. You should find that 15 makes everything add up to 180. Now knowing x is 15 now we know that 3x is equal to 45. So k=45 That is how you solve this tricky question. Hope this helps! ❤️
Answer:
x=2,y=−1
Step-by-step explanation:
Solve for y in the first equation.
y=−9x/11+7/11
0=−2y+10−6x
Replace all occurrences of y with −9x/11+7/11 in each equation.
0=−48(x−2)11
y=−9x11+711
Solve for x in the first equation.
x=2
y=−9x/11+7/11
Replace all occurrences of x with 2 in each equation.
y=−1
x=2
The solution to the system is the complete set of ordered pairs that are valid solutions.
(2,−1)
The result can be shown in multiple forms.
Point Form:
(2,−1)
Equation Form:
x=2,y=−1
Answer:
18%
Step-by-step explanation:
From adjusted gross income of $100,000, subtract the standard deduction of $6,350 and a single personal exemption of $4,050. That makes taxable income equal to $89,600. That amount is just below the upper end of the 25% tax bracket, with the tax calculation amounting to $18,138.75. That works out to an effective tax rate of 18%.
Answer:
-11,3
Step-by-step explanation: using foil (x-2)(X+10)=x^2+8x-20
x^2+8x-20-13=13-13 X^2+8x-33=0 factoring you get (x+11)(x-3)=0 so x+11=0
x-3=0
x=-11,3
if you found this helpful please thank me
Answer:
Explanation:
f(3) = (3 - 1) • 3/2
f(3) = 2 • 3/2
f(3) = 3
f(4) = (4 - 1) • 3/2
f(4) = 3 • 3/2
f(4) = 9/2
f(5) = (5-1) • 3/2
f(5) = 4 • 3/2
f(5) = 6
f(6) = (6-1) • 3/2
f(6) = 5 • 3/2
f(6) = 15/2
f(7) = (7-1) • 3/2
f(7) = 6 • 3/2
f(7) = 9